Analysis of Information and Communication Technology (ICT) Learning Evaluation within the Context of the Kurikulum Merdeka (Independent Curriculum) - Zulfani Sesmiarni; Roma Angelina; Misriyati; Yarozaktul Fauziah; Silvia Nova (SAFE-Network, 2026)
This research aims to analyze the evaluation of Information and Communication Technology (ICT) learning for class VII students in the context of the Merdeka Curriculum at SMPN 3 Payakumbuh. The research method used was descriptive qualitative with class VII student participants. Data was collected through direct observation, especially during the Mid-Term Examination (UTS) on November 29, 2023. Evaluation results include students' average scores and grouping of scores into categories. Analysis shows that a number of students need increased enthusiasm for learning, with the highest percentage in the very high category. The research conclusions emphasize the need for additional guidance and the role of parents in improving student preparation before learning activities. Learning evaluation also highlights that the quality of learning still needs to be considered so that it is in line with the expectations of the Independent Curriculum. Therefore, collaboration between schools, teachers and parents needs to be improved to ensure optimal student preparation and learning outcomes, especially in the implementation of the Independent Curriculum.